2017
DOI: 10.1021/jacs.6b11450
|View full text |Cite
|
Sign up to set email alerts
|

Hidden States within Disordered Regions of the CcdA Antitoxin Protein

Abstract: The bacterial toxin-antitoxin system CcdB-CcdA provides a mechanism for the control of cell death and quiescence. The antitoxin CcdA protein is a homodimer composed of two monomers that each contain a folded N-terminal region and an intrinsically disordered C-terminal arm.Binding of the intrinsically disordered C-terminal arm of CcdA to the toxin CcdB prevents CcdB from inhibiting DNA Gyrase and thereby averts cell-death. Accurate models of the unfolded state of the partially disordered CcdA antitoxin can ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Full-length SGS-CcdA was stable in the presence of TldD/E in vitro ( Figure S2 A), but SGS-CcdA41 was readily degraded to small peptides ( Figure S2 B). CcdA41 is an intrinsically disordered C-terminal tail of CcdA, and previous studies have shown that it is more susceptible to cleavage by Lon protease compared with the full-length protein, presumably due to the lack of interactions with N-terminal folded domain ( Burger et al., 2017 , Van Melderen et al., 1996 ). Hence our results support earlier western blot data showing stabilization of Ccd41 in tld mutants ( Allali et al., 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Full-length SGS-CcdA was stable in the presence of TldD/E in vitro ( Figure S2 A), but SGS-CcdA41 was readily degraded to small peptides ( Figure S2 B). CcdA41 is an intrinsically disordered C-terminal tail of CcdA, and previous studies have shown that it is more susceptible to cleavage by Lon protease compared with the full-length protein, presumably due to the lack of interactions with N-terminal folded domain ( Burger et al., 2017 , Van Melderen et al., 1996 ). Hence our results support earlier western blot data showing stabilization of Ccd41 in tld mutants ( Allali et al., 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…CcdA is one such molecular switch that restores gyrase function by facilitating extraction of CcdB from its complex with GyrA14. The conformational state of the disordered C-terminal domain of CcdA regulates its recognition by Lon protease, and is also involved in binding to CcdB (Burger et al, 2017;Drobnak et al, 2013;Madl et al, 2006). Binding of CcdA to CcdB inhibits CcdB toxicity as well as autoregulating transcription of the ccd operon (De Jonge et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have carried out detailed experimental studies of one such molecular switch, CcdA, which is known to restore the function of Gyrase by facilitating dissociation of CcdB from the CcdB:GyrA14:DNA complex (Dao-Thi et al, 2005; De Jonge et al, 2009). The disordered C-terminal domain of CcdA is involved in binding to CcdB, thereby inhibiting CcdB toxicity and autoregulating the transcription of the ccd operon (Burger et al, 2017; Drobnak et al, 2013; Madl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%